Optimization of energy‐capture performance of point‐absorber wave energy converter. (3rd March 2022) - Zhang, Baocheng; Deng, Ziwei; Miao, Yu; Zhao, Bo; Wang, Qiang; Zhang, Kaisheng
Summary: An optimization process is proposed for improving the energy‐harvesting efficiency of the point‐absorber wave energy converter (WEC) and thus enhancing the utilization of wave energy resources. The multidisciplinary design optimization integration system ISIGHT is adopted to establish an optimization design flow for the shape parameters of the point‐absorber WEC. The motion equations of the point‐absorber WEC are established according to the potential flow theory, and the wave energy capture capacity per unit is calculated. Considering it as the objective, the point‐absorber WEC is modified to improve the energy‐capture efficiency by using an optimization function in an approximation model. A comparison indicates that a cylindrical‐bottom point‐absorber WEC with a diameter of 7 m, draft of 1.8 m, and damping factor of 31 150 Ns·m −1 has the optimal performance and the maximum energy capture capacity. The energy‐capture performance of the WEC can be significantly enhanced through this optimization method. Abstract : An optimization process is proposed for improving the energy‐harvesting efficiency of the point‐absorber WEC and thus enhancing the utilization of wave energy resources. The method integrates experimental design, approximate modeling, and algorithmic optimization. A comparison indicates that a cylindrical‐bottom point‐absorber WEC with a diameter of 7 m, draft of 1.8 m, and damping factor of 31 150 Ns·m −1 has the optimal performance and the maximum energy capture capacity. The energy‐capture performance of the WEC can be significantly enhanced through this optimization method.